2011
DOI: 10.17705/1cais.02927
|View full text |Cite
|
Sign up to set email alerts
|

Maturity Models in Information Systems Research: Literature Search and Analysis

Abstract: This article collects and analyzes seventy-six maturity model articles that have been published in leading Information Systems (IS) journals and conference proceedings during the past fifteen years. We study the IS literature on maturity models from three different perspectives: a research perspective, which is particularly relevant for scholars who are interested in the design and adoption of maturity models; a publication perspective, which reflects the interests of authors and reviewers of maturity model ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 77 publications
0
97
0
5
Order By: Relevance
“…The typical approach used in these models is that a business is expected to follow a logical path through distinct stages to achieve business transformation. Poeppelbuss et al (2011) suggested that these stage models fall into the category of maturity models.…”
Section: Introductionmentioning
confidence: 99%
“…The typical approach used in these models is that a business is expected to follow a logical path through distinct stages to achieve business transformation. Poeppelbuss et al (2011) suggested that these stage models fall into the category of maturity models.…”
Section: Introductionmentioning
confidence: 99%
“…Maturity models are frequently applied in organizations to assess the current state of development against some notional 'best state' and then to determine improvement measures to reach the desired best state (Poppelbuß et al, 2011).…”
Section: Imandt In the Nhs-a Maturity Model Lensmentioning
confidence: 99%
“…Maturity models are a tool for capability development that has become increasingly popular over the last few decades (Harmon, 2009;Pöppelbuß et al, 2011). Based on the assumption of predictable patterns of evolution and change, maturity models foster the development of capabilities along a path of predefined stages (Mettler, 2011).…”
Section: Process Maturity Modelsmentioning
confidence: 99%
“…One of the most popular tools from the BPM area that supports capability development is process maturity models (Pöppelbuß, Niehaves, Simons, & Becker, 2011). Although process maturity models recommend which capabilities an organization should develop, most of them do not help assess the extent to which capabilities should be developed.…”
Section: Introductionmentioning
confidence: 99%